El giro dependentista latinoamericano Los orígenes de la teoría marxista de la Dependencia - Cristóbal Cárdenas Castro, Juan; Lana Seabra, Raphael (Ariadna Ediciones, 2022)
The great merit and originality of this book lies in the fact that it analyzes the process of the creation of the Marxist theory of dependency by investigating the writings of its founders, now deceased, and through the current reflections of several of its closest collaborators. The current generations of students and researchers may not know this theory and its significance or only have a vague idea about it because it was formulated more than half a century ago and was displaced by the neoliberal dogmatic turn. I invite you to read this book to respond to current challenges by rescuing and renewing Latin American critical thinking (Cristobal Kay).